Answer:
Answer: (0, -4) and (6, 1)
• x(t) = 6t --- equation (a)
• y(t) = 3t - 2 --- equation (b)
→ From equation (a), make t the subject:
[tex]→ \: { \tt{x(t) = 6t }} \\ \\ → \: { \tt{t = \frac{x(t)}{6} }}[/tex]
• substitute for t in equation (b)
[tex]→ \: { \tt{y(t) = 3(\frac{x(t)}{6}) - 2 }} \\ \\ → \: { \tt{y(t) = \frac{x(t)}{2} - 2 }}[/tex]
• Assume t is 1:
[tex]→ \: { \tt{y = \frac{x}{2} - 2}} \\ \\ → \: { \boxed{ \tt{2y = x - 4}}}[/tex]
• when x is zero, y is -4
[tex]→ \: { \tt{2y = 0 - 4 = - 4}} \\ [/tex]
• when x is 6, y is 1
[tex]→ \: { \tt{2y = 6 - 4 = 2 }} \\ { \tt{y = 1}}[/tex]